2018
DOI: 10.1007/s10529-018-2614-4
|View full text |Cite
|
Sign up to set email alerts
|

COX6B1 relieves hypoxia/reoxygenation injury of neonatal rat cardiomyocytes by regulating mitochondrial function

Abstract: ObjectiveMitochondrial dysfunction plays a pivotal role in various pathophysiological processes of heart. Cytochrome oxidase subunit 6B1 (COX6B1) is a subunit of cytochrome oxidase.MethodsCardiomyocytes were isolated from neonatal SD rats (within 24 h of birth) by repeating digestion of collagenase and trypsin. COX6B1 over-expression and hypoxia/reoxygenation was conducted on neonatal rat cardiomyocytes. Cell viability, apoptosis rates, mitochondria membrane potential and mitochondrial permeabilization transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
(36 reference statements)
1
15
1
Order By: Relevance
“…The proteomics analysis demonstrated that several molecular pathways associated with the inhibitory effects of Xe administration on NLRP3 inflammasome-mediated signaling and other inflammatory reactions may contribute to the mechanism of action of the potential renoprotective effects of Xe in the treated ASLN mice. Specifically, in the present study, we found an upregulated oxidative phosphorylation pathway, encoded by several genes, including COX6B1 38,50 , in the Xetreated ASLN mice. In this regard, COX6B1 is a subunit of cytochrome oxidase in mitochondria and plays a protective role in cardiomyocyte injury by reducing ROS production.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The proteomics analysis demonstrated that several molecular pathways associated with the inhibitory effects of Xe administration on NLRP3 inflammasome-mediated signaling and other inflammatory reactions may contribute to the mechanism of action of the potential renoprotective effects of Xe in the treated ASLN mice. Specifically, in the present study, we found an upregulated oxidative phosphorylation pathway, encoded by several genes, including COX6B1 38,50 , in the Xetreated ASLN mice. In this regard, COX6B1 is a subunit of cytochrome oxidase in mitochondria and plays a protective role in cardiomyocyte injury by reducing ROS production.…”
Section: Discussionsupporting
confidence: 66%
“…In this regard, COX6B1 is a subunit of cytochrome oxidase in mitochondria and plays a protective role in cardiomyocyte injury by reducing ROS production. 38 This finding further supports the likelihood that the therapeutic effects of Xe treatment involved inhibition of ROS production, although it is worth pursuing the exact role of COX6B1 and related molecular mechanisms in the LN mice.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As a cytochrome oxidase subunit, COX6B1 is encoded in the nuclear genome and serves critical roles in energy metabolism and regulation (50). It has been demonstrated that COX6B1 overexpression inhibits apoptosis and induces mitochondrial respiration and stress resistance (35,51). Accordingly, COX6B1 upregulation in glioma may be a response of the glioma cells to increase their resistance to a harsh environment.…”
Section: Discussionmentioning
confidence: 99%
“…COX6B1 protein may be associated with the development of the central nervous system (16). Previous studies reported that COX6B1 may protect the myocardium against I/R injury by regulating mitochondrial function (20,21); however, whether COX6B1 protects hippocampal neurons against I/R injury has not been reported, and the molecular mechanisms underlying the role of COX6B1 in the development of the nervous system remains unclear.…”
Section: Introductionmentioning
confidence: 99%